BUDAYA PROFETIK DI PESANTREN SALAF - Dinda Wulan Afriani (IBDA` : Jurnal Kajian Islam dan Budaya, 2013)
This paper reveals the prophetic culture in Islamic boarding school.The culture is implemented by kiai as the heir of prophet's knowledge.Kiai becomes the central figure who has some concepts which followsthe prophet's attitude. In boarding school there are also some values todo goodness, to live in harmony. There are seven patterns of life whichare in accordance with the prophet's attitude; modesty, togetherness, independenceand responsibility, consistence, discipline, and sincerity.